Simple proxies for estimating the concentrations of monoterpenes and their oxidation products at a boreal forest site - Kontkanen, Jenni; Paasonen, Pauli; Aalto, Juho; Bäck, Jaana; Rantala, Pekka; Petäjä, Tuukka; Kulmala, Markku (COPERNICUS GESELLSCHAFT MBH, 2016)
The oxidation products of monoterpenes likely have a crucial role in the formation and growth of aerosol particles in boreal forests. However, the continuous measurements of monoterpene concentrations are usually not available on decadal timescales, and the direct measurements of the concentrations of monoterpene oxidation product have so far been scarce. In this study we developed proxies for the concentrations of monoterpenes and their oxidation products at a boreal forest site in Hyytiala, southern Finland. For deriving the proxies we used the monoterpene concentration measured with a proton transfer reaction mass spectrometer (PTR-MS) during 2006-2013. Our proxies for the monoterpene concentration take into account the temperature-controlled emissions from the forest ecosystem, the dilution caused by the mixing within the boundary layer and different oxidation processes. All the versions of our proxies captured the seasonal variation of the monoterpene concentration, the typical proxy-to-measurements ratios being between 0.8 and 1.3 in summer and between 0.6 and 2.6 in winter. In addition, the proxies were able to describe the diurnal variation of the monoterpene concentration rather well, especially in summer months. By utilizing one of the proxies, we calculated the concentration of oxidation products of monoterpenes by considering their production in the oxidation and their loss due to condensation on aerosol particles. The concentration of oxidation products was found to have a clear seasonal cycle, with a maximum in summer and a minimum in winter. The concentration of oxidation products was lowest in the morning or around noon and highest in the evening. In the future, our proxies for the monoterpene concentration and their oxidation products can be used, for example, in the analysis of new particle formation and growth in boreal environments. Peer reviewed